The votes are in: a process for selecting reference books and managing the reference budget. Issue 3 (4th July 2016) - Collins, Susan L.
Abstract : Purpose: The purpose of this study is to describe the process that is used for selecting reference books and managing the reference budget at one academic library reference unit. While there have been articles written on reference collection development, none have explained the process in detail. Design/methodology/approach: This paper describes the process used to select reference books via a voting system and how the budget is managed over ordering periods. Findings: Using the system described, librarians can effectively manage a reference budget that fairly distributes resources across different subjects and gives selectors greater control of the resources they purchase. Originality/value: This is a unique book selection and ordering system that has not been described in the literature.